2011
DOI: 10.5539/ijms.v3n1p78
|View full text |Cite
|
Sign up to set email alerts
|

The Extent to Which Jordanian Doctors and Nurses Perceive the Accreditation in Private Hospitals

Abstract: This study aims to know if the doctors and nurses in the Jordanian private hospitals have a perception about the accreditation, and if there's a different between the doctors and nurses perception and understanding the accreditation standard at their hospitals. The results of this study showed that Doctors and nurses have a positive attitude regarding their perception of accreditation standards, Related to the Management and leadership, Strategic planning for quality, Human Resources utilization, Quality Manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 11 publications
2
10
0
6
Order By: Relevance
“…However, this study was focusing on the nursing staff from 22 hospital units in Saudi Arabia, therefore it indicated that the results of all four types of information obtained by this study showed an overall highly significant positive attitude toward the application of the process of accreditation (Al Awa et al, 2011). Likewise, research was carried out to investigate the perception of accreditation by doctors and nurses in Jordanian private hospitals, and indicated that doctors' and nurses' attitudes toward hospital accreditation standards are positive (Diab, 2011).…”
Section: Hospital Accreditation (Ha)mentioning
confidence: 94%
“…However, this study was focusing on the nursing staff from 22 hospital units in Saudi Arabia, therefore it indicated that the results of all four types of information obtained by this study showed an overall highly significant positive attitude toward the application of the process of accreditation (Al Awa et al, 2011). Likewise, research was carried out to investigate the perception of accreditation by doctors and nurses in Jordanian private hospitals, and indicated that doctors' and nurses' attitudes toward hospital accreditation standards are positive (Diab, 2011).…”
Section: Hospital Accreditation (Ha)mentioning
confidence: 94%
“…However, notwithstanding the commonly accepted perceptions by governments (El-Jardali et al, 2008) and healthcare professionals (Diab, 2011;El-Jardali et al, 2008) on the benefits of accreditation; existing evidence is either modest Lutfiyya et al, 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 r n a l o f H e a l t h O r g a n i z a t i o n a n d M a n a g e m e 3 2009) or inconclusive (Bogh et al, 2015;Braithwaite et al, 2010;Dean Beaulieu and Epstein, 2002;Greenfield and Braithwaite, 2008;Miller et al, 2005;Shaw et al, 2010;Thornlow and Merwin, 2009), particularly regarding its impact on the quality of care. For example, findings from a study of 216 state psychiatric hospitals in the U.S. revealed a weak association between accreditation and the seven indicators of quality of care selected (average cost per patient, per diem bed cost, total staff hours per patient, clinical staff hours per patient, percent of staff hours provided by medical staff bed turnover, and percent of beds occupied) (Hadley and McGurrin, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Os hospitais têm enfrentado desafios em termos de redução de custos, aumento da qualidade e da segurança dos pacientes, que demandam a busca constante pela melhoria dos processos e estimulam a busca pela acreditação hospitalar (Diab, 2011;Greenfield et al, 2011;Ritz, 2009). Além disso, a acreditação é buscada pelas organizações para, através da melhoria dos processos, racionalizar a utilização dos recursos e, consequentemente, afetar positivamente os resultados financeiros da instituição (Greenfield, & Braithwaite, 2008;Shaw, 2004).…”
Section: Melhoria De Processosunclassified
“…Para diversos autores, um dos maiores motivadores para os hospitais buscarem a acreditação é a preocupação em aumentar a segurança dos pacientes (Chassin, 2008;Giraud-Roufast, & Chabot, 2008;Seabra, 2007;Shaw, 2004;Turner, 2011). A acreditação aumentaria a segurança do paciente através do controle de processos críticos como prontuário do paciente, protocolos de conduta clínica e monitoramento de efeitos adversos (Chassin, 2008;Diab, 2011;Turner, 2011). Neste sentido, os resultados da pesquisa realizada por Sekimoto et al (2008) junto a hospitais universitários apontam que um dos grandes benefícios da acreditação é o impacto positivo no controle de infecções hospitalares.…”
Section: Melhoria De Processosunclassified
See 1 more Smart Citation